2003
DOI: 10.1088/1475-7516/2003/04/004
|View full text |Cite
|
Sign up to set email alerts
|

Upper limits on neutrino masses from the 2dFGRS and WMAP: the role of priors

Abstract: Abstract. Solar, atmospheric, and reactor neutrino experiments have confirmed neutrino oscillations, implying that neutrinos have non-zero mass, but without pinning down their absolute masses. While it is established that the effect of neutrinos on the evolution of cosmic structure is small, the upper limits derived from large-scale structure could help significantly to constrain the absolute scale of the neutrino masses. In a recent paper the 2dF Galaxy Redshift Survey (2dFGRS) team provided an upper limit m … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
42
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 75 publications
2
42
1
Order By: Relevance
“…Still, the precise analysis of the recent microwave background anisotropy data and structure data at large red-shifts imply the necessity of some admixture of hot DM which can be naturally provided by light neutrinos with Σm ν f < 2.2 eV or m ν f < 0.73 eV (see for example [29,30]). Recent WMAP measurements (see [31]) together with the LSS analysis has improved the limit: Σm ν f < 0.69 eV and hence, m ν f < 0.23 eV.…”
Section: Large Scale Structure and Neutrinomentioning
confidence: 99%
“…Still, the precise analysis of the recent microwave background anisotropy data and structure data at large red-shifts imply the necessity of some admixture of hot DM which can be naturally provided by light neutrinos with Σm ν f < 2.2 eV or m ν f < 0.73 eV (see for example [29,30]). Recent WMAP measurements (see [31]) together with the LSS analysis has improved the limit: Σm ν f < 0.69 eV and hence, m ν f < 0.23 eV.…”
Section: Large Scale Structure and Neutrinomentioning
confidence: 99%
“…When m ν > 10 −3 eV neutrinos are non-relativistic today [11] and thus behave like a hot component of dark matter. The presence of even a small fraction of massive neutrinos (hot dark matter) f ν ≡ Ω ν /Ω M , of order 10-20 %, requires a smaller value for the cosmological constant in comparison to a pure ΛCDM model, while other cosmological parameters are largely unaffected [6]. This is because a smaller Ω Λ results in a larger Ω M and hence a faster fluctuation growth rate, which compensates for the reduction of small-and intermediate-scale power caused by the neutrinos.…”
mentioning
confidence: 99%
“…To compute P (k, z) we assume a close to scaleinvariant (Harrison-Peebles-Yu-Zeldovich) post-inflation energy density perturbation power spectrum P 0 (k) ∝ k n , with n ∼ 1, and we use a semi-analytical approximation for the transfer function T (k, z) in the ΛCDM model with three species of equal-mass neutrinos [41]. 6 For the 5 This is more consistent with estimates from WMAP data and from Big Bang nucleosynthesis using the mean of the primordial deuterium abundance measurements, but it is significantly larger than an estimate based on helium and lithium abundance measurements, see, e.g., Ref. [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, m 0 is constrained by WMAP data [10],3m 0 < 0.71 eV. When analyzed in conjunction with neutrino oscillation, it is found that mass eigenvalues are essentially degenerate with 3m 0 > 0.4 eV [11] The above limits put limits on ε : 7.9 × 10 −3 < ε < 2.5 × 10 −2 . It is pertinent to remark that in view of small mass differences involved [cf.…”
mentioning
confidence: 99%